Kompetencje zawodowe a system praktyk w kształceniu studentów informacji naukowej i bibliotekoznawstwa - Gruchała, Irena; Stanula, Małgorzata (Biblioteka Uniwersytecka w Poznaniu, 2013)
Praktyki zawodowe są ważnym elementem kształcenia na kierunku informacja naukowa i bibliotekoznawstwo. Istotnie wpływają na poszerzenie kompetencji zawodowych studentów, co w przyszłości decyduje o możliwości ich zatrudnienia. W niniejszym artykule podjęto analizę realizacji praktyk na przestrzeni ostatnich ośmiu lat (2004/2005–2011/2012) w Instytucie Informacji Naukowej i Bibliotekoznawstwa Uniwersytetu Jagiellońskiego, na podstawie dokumentacji zgromadzonej w instytucie. W analizie brano pod uwagę miejsca praktyk, rodzaje instytucji, w których one przebiegały, oraz opinie opiekunów praktyk i studentów. Przedstawiono także zmiany w programach praktyk, wynikające z wdrażania nowego programu kształcenia w instytucie, opracowanego zgodnie z Krajowymi Ramami Kwalifikacji dla Szkolnictwa Wyższego, oraz ich wpływ na szanse absolwentów na rynku pracy.

Traineeship programs constitute an important element in higher education in research information and librarianship. They significantly influence and improve professional competence of students, which may turn out to be decisive in their prospective employment. The present article attempts to analyze the quality the traineeship program offered by the Institute of Research Information and Librarianship at the Jagiellonian University within the time frame of the past eight years (2004/2005-2011/2012). The analysis is based on the available documentation kept at the institute. The analysis includes a review of the location of placements, types of host institutions and opinions of traineeship programs supervisors and students involved. In addition, the changes introduced to the traineeship program resulting from the implementation of a new curriculum at the institute, devised according to the All-National Framework of Professional Qualifications for higher education institutions, are presented and discussed. The article is concluded with a discussion on the possible influence of traineeship program upon future chances of employment on the labour market.
Professional competences vs. traineeship system in education of students of research information and librarianship
Keywords: kompetencje zawodowe; praktyki studenckie; Instytut INiB UJ; informacja naukowa i bibliotekoznawstwo; professional competences; student traineeships; Institute of Research Information and Book Studies at the Jagiellonian University; research information and librarianship